Managers’ and Investors’ Responses to Media Exposure of Board Ineffectiveness - Joe, Jennifer R.; Louis, Henock; Robinson, Dahlia (Journal of Financial and Quantitative Analysis, 2009)
Abstract We analyze the impact of the press on the behavior of various economic agents by examining how media exposure of board ineffectiveness affects corporate governance, investor trading behavior, and security prices. Our focus on board quality is motivated by the strong media criticism to which corporate boards and corporate America, in general, have been recently subjected. The results indicate that media releases of (noisy) information have significant economic consequences. In particular, media exposure of board ineffectiveness forces the targeted agents to take corrective actions and enhances shareholder wealth. Individual investors appear to react negatively to the media exposure, whereas investment firms act as if they anticipate the targeted firms’ corrective actions.